New Code Subject Files
The records contain clippings from the Soviet (after 1991, Russian) and Western press, news agency releases, TV and radio monitoring materials. The series comprises information on the following topics: ecology, economics, mass media, culture, politics, science, security policy, social issues in the countries of the former Soviet Union.